(untitled) (Pedagogy of Higher and Secondary Education, 2007)
We consider the problem of the picture formation in a relationship with the law of the tri-componentness of the lightnings by undergraduate students in fine arts. It is shown that the space representation essentially depends from the conscious relationships between the form and the background.